Exposure to ambient air pollution and blood lipids in children and adolescents: A national population based study in China. (November 2020) - Gui, Zhao-Huan; Yang, Bo-Yi; Zou, Zhi-Yong; Ma, Jun; Jing, Jin; Wang, Hai-Jun; Dong, Guang-Hui; Ma, Ying-Hua; Guo, Yu-Ming; Chen, Ya-Jun
Abstract: Few studies have explored the links of air pollution and childhood lipid profiles and dyslipidemias. We aimed to explore this topic in Chinese children and adolescents. This study included 12, 814 children aged 7–18 years who participated in a national survey in 2013. Satellite-based spatial-temporal model was used to predict 3-y (2011–2013) average particles with diameters ≤ 1.0 μm (PM1 ), ≤2.5 μm (PM2.5 ), ≤10 μm (PM10 ), and nitrogen dioxide (NO2 ) concentrations. Generalized linear mixed models were employed to evaluate the relationships of air pollution and total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and dyslipidemias. Every 10 μg/m 3 increase in PM1, PM2.5, PM10, and NO2 was related to increases of 6.20% [95% confidence interval (CI): 2.44, 10.10], 5.31% (95%CI: 0.41, 10.44), 3.49% (95%CI: 0.97, 6.08), and 5.25% (95%CI: 1.56, 9.07) in TC, respectively. The odds ratio of hypercholesterolemia associated with a 10 μg/m 3 increase in PM1, PM2.5, and NO2 was 2.15 (95%CI: 1.27, 3.65), 1.70 (95%CI: 1.12, 2.60), and 1.43 (95%CI: 1.05, 1.93), respectively. No associations were found for air pollution and other blood lipids. Long-term PM1, PM2.5, PM10, and NO2 exposures were positively associated with TC levels and risk of hypercholesterolemia in children and adolescents. Graphical abstract: Image 1 Highlights: We studied 12, 814 Chinese children in a national cross-sectional study. Associations between ambient air pollution and blood lipids were examined. PM1, PM2.5, PM10, and NO2 were positively associated with total cholesterol. PM1, PM2.5, and NO2 were positively related to risk of hypercholesterolemia. Abstract : Main findings: Long-term PM1, PM2.5, PM10, and NO2 exposures were positively associated with TC levels and risk of hypercholesterolemia in children and adolescents.